Report of The NDC Committee on Employment - Planning Commission (Planning Commission, 1992)
Employment generation is a major issue before the country in the last decade of this century. For a variety of reasons employment generation has come to occupy the centre-stage in our development planning as well as implementation. First, the incidence of poverty, even though having declined significantly over the years, continues to be high, and for a large mass of the poor, gainful employment alone provides the way for alleviation of poverty. Second, a larger and more efficient use of the abundantly available labour could be the most effective way for the Indian economy to grow faster and become internationally competitive. Third, unemployment, particularly of the educated, involves not only a wastage of human capital, but also endangers social and political stability in so far as the educated youth, in the absence of productive engagement, can get frustrated and indulge in anti-social activities.
Planning Commission
Planning Commission